The Effectiveness of Using the Photomath Application in Enhancing Students’ Learning Interest - Maydawati, Layli; Wahyuni, Molli; Astuti, Astuti (Journal of Mathematics Science and Computer Education, 2024)
This article examined the effectiveness of using the Photomath application in enhancing the learning interest of Grade VIII students at SMP Negeri 8 Tapung. This study analyzed students' learning interests before and after using the Photomath application. The research employed a quasi-experimental design. Purposive sampling was used to select participants, consisting of 23 students from grade VIII C. Data were collected through documentation, surveys, and observations. The findings of this study indicated an increase in the average score of the learning interest questionnaire. Before using the Photomath application, the average score was 54.592, categorized as low interest. After using the Photomath application, the average score increased to 55.62. Based on the calculation of the average scores from both data sets, it was concluded that H0 was accepted and Ha was rejected. This meant that there was no significant difference in average learning outcomes between the experimental group and the control group. These findings suggested that Grade VIII students at SMP Negeri 8 Tapung showed limited interest in learning using the Photomath application.